Marketing management as a strategic part of sustainable development in the conditions of rural tourism in Slovakia - Holienčinová, Mária; Holota, Tomáš (Turystyka i Rozwój Regionalny, 2018)
While the rural tourism is widespread in the world, in Slovakia has just started to develop in recent years. Rural tourism supports small and medium-sized enterprises, with profits remaining in the region. A challenge for ensuring sustainable development in rural areas is to cover the development needs of the community. Rural tourism has been indicated as a good development strategy for Slovak rural areas. It is a great opportunity for those who not only love the region but also are interested in its comprehensive development- in the form of providing services. These strategic goals cannot be achieved without modern approaches and forms of marketing management. Destination management fully supported by the right marketing principles is the only way how to increase income from tourism and enhance the region. The main aim of this paper is to point out the importance of marketing in the process of the sustainable rural tourism development. Key findings indicate that marketing provides the guidance and ideas for further improvements in the sector of rural tourism.